Edukasi Ibu Hamil Tentang Pentingnya Pemeriksaan Usg dan Pelaksanaan Pemeriksaan USG Di Klinik Sartika Manurung - Eka Ristin Tarigan; Adelina Fitri Tanjung; Erinda Pasaribu; Damai Putri Sari Siahaan (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
Pregnant women's lack of understanding of the importance of antenatal care (ANC) can negatively impact fetal development. The use of ultrasound technology during ANC examinations can provide a more accurate picture of fetal condition. Ultrasound can determine whether the fetus' size is within normal limits, the number of fetuses, the volume of amniotic fluid, the position of the placenta, and whether the fetus' weight is appropriate, larger, or smaller than the gestational age. Objective: To increase pregnant women's knowledge of the importance of ANC examinations and to evaluate fetal condition by providing free ultrasound services. Methods: To conduct outreach activities, including free ultrasound examinations. This activity involved 22 pregnant women from the community surrounding the service location. Results: After the implementation, participants' knowledge test scores increased. The outreach program ran smoothly and participants were very enthusiastic, as evidenced by the many questions asked. All participants participated in the free ultrasound examinations, which showed healthy and normal fetal condition. Conclusion: This outreach program was effective in increasing pregnant women's understanding of the importance of ANC examinations, while the free ultrasound examinations helped confirm fetal health. All participants participated enthusiastically in the activity, and the benefits were felt by all parties involved..